2010
DOI: 10.1016/j.cellimm.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The roles of IL-12 and IL-23 in CD8+ T cell-mediated immunity against Listeria monocytogenes: Insights from a DC vaccination model

Abstract: Listeria monocytogenes infection induces a strong inflammatory response characterized by the production of IL-12 and IFN-γ and protective immunity against this pathogen is dependent on CD8 + T cells (CTL). Recent studies have suggested that these inflammatory cytokines affect the rate of memory CD8+ T cell generation as well as the number of short lived effector cells generated. The role of the closely related cytokine, IL-23, in this response has not been examined. We hypothesized that IL-12 and IL-23 produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 65 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…The ability of IL-6-deficient DCs to promote the generation of functional CD8 + Tm cells indicates that other soluble factors (IL-12 and IL-23) produced by DCs are sufficient to induce the generation of CD8 + Tm cells. Indeed, it was shown by others that vaccination with IL-12 and IL-23 deficient DCs abrogated CD8 + Tm-cell development [44]. It is also possible that IL-6 plays a role during CD8 + Tm-cell differentiation but that it does not have to be produced by the APCs involved in the T cell priming.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of IL-6-deficient DCs to promote the generation of functional CD8 + Tm cells indicates that other soluble factors (IL-12 and IL-23) produced by DCs are sufficient to induce the generation of CD8 + Tm cells. Indeed, it was shown by others that vaccination with IL-12 and IL-23 deficient DCs abrogated CD8 + Tm-cell development [44]. It is also possible that IL-6 plays a role during CD8 + Tm-cell differentiation but that it does not have to be produced by the APCs involved in the T cell priming.…”
Section: Resultsmentioning
confidence: 99%
“…The data obtained from these studies strongly suggest that IL-15 is a pivotal cytokine which protects the animals against Toxoplasma rechallenge Moreover, the data shows there is no redundant mechanism responsible for the generation of robust CD8 + T cell immunity in rechallenged IL-15 deficient animals. This is surprising, since apart from IL-7 and IL-15 other γ c family members like IL-2 [36, 37], IL-4 [38, 39], IL-12 [40, 41] and IL-21 [42] have been implicated in CD8 memory generation in other infectious disease models. Unlike other pathogens, T. gondii infection does not induce a potent IL-2 response even during the acute phase of infection [11, 43-45], thus discounting its role in the induction of CD8 + T cell response against T.gondii .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other pathogens, T. gondii infection does not induce a potent IL-2 response even during the acute phase of infection [11, 43-45], thus discounting its role in the induction of CD8 + T cell response against T.gondii . IL-12 is another important cytokine known to regulate the development of memory CD8 + T cell response [40, 41]. In a recent report it has been demonstrated that high IL-12 levels induced during Listeria monocytogenes infection down-regulates CD8 + T cell memory differentiation [46].…”
Section: Discussionmentioning
confidence: 99%
“…The improved the efficacy of DC vaccines in mice, suggested the significance of IL-12 in augmenting CTL-mediated cytotoxicity. 29,30 TNF-α was shown to have antiinflammatory properties, and it can directly limit T cell-mediated responses via apoptosis or indirectly via regulation of IL-12, a major mediator in type 1 inflammatory response. [31][32][33] The production of IL-12 and TNF-α, which were cytokines associated Downloaded by [41.190.164.64] at 12:11 08 October 2015 maintain memory.…”
Section: Discussionmentioning
confidence: 99%